The crimson crown - Walter, Heather, 1987- (Walter, Heather, 1987- Crimson crown duology, 2024)
"Mirror, mirror on the wall, who's the greatest villain of them all? Snow White's dark queen tells her side of the story in this queer, witchy re-imagining of the classic fairy tale from the author of Malice"--